Identifying Molecular Properties of Ataxin-2 Inhibitors for Spinocerebellar Ataxia Type 2 Utilizing High-Throughput Screening and Machine Learning - Smita Sahay; Jingran Wen; Daniel R. Scoles; Anton Simeonov; Thomas S. Dexheimer; Ajit Jadhav; Stephen C. Kales; Hongmao Sun; Stefan M. Pulst; Julio C. Facelli; David E. Jones (Biology)
Spinocerebellar ataxia type 2 (SCA2) is an autosomal dominant neurodegenerative disorder marked by cerebellar dysfunction, ataxic gait, and progressive motor impairments. SCA2 is caused by the pathologic expansion of CAG repeats in the ataxin-2 (ATXN2) gene, leading to a toxic gain-of-function mutation of the ataxin-2 protein. Currently, SCA2 therapeutic efforts are expanding beyond symptomatic relief to include disease-modifying approaches such as antisense oligonucleotides (ASOs), high-throughput screening (HTS) for small molecule inhibitors, and gene therapy aimed at reducing ATXN2 expression. In the present study, data mining and machine learning techniques were employed to analyze HTS data and identify robust molecular properties of potential inhibitors of ATXN2. Three HTS datasets were selected for analysis: ATXN2 gene expression, CMV promoter expression, and biochemical control (luciferase) gene expression. Compounds displaying significant ATXN2 inhibition with minimal impact on control assays were deciphered based on effectiveness (E) values (n = 1321). Molecular descriptors associated with these compounds were calculated using MarvinSketch (n = 82). The molecular descriptor data (MD model) was analyzed separately from the experimentally determined screening data (S model) as well as together (MD-S model). Compounds were clustered based on structural similarity independently for the three models using the SimpleKMeans algorithm into the optimal number of clusters (n = 26). For each model, the maximum response assay values were analyzed, and E values and total rank values were applied. The S clusters were further subclustered, and the molecular properties of compounds in the top candidate subcluster were compared to those from the bottom candidate subcluster. Six compounds with high ATXN2 inhibiting potential and 16 molecular descriptors were identified as significantly unique to those compounds (p < 0.05). These results are consistent with a quantitative HTS study that identified and validated similar small-molecule compounds, like cardiac glycosides, that reduce endogenous ATXN2 in a dose-dependent manner. Overall, these findings demonstrate that the integration of HTS analysis with data mining and machine learning is a promising approach for discovering chemical properties of candidate drugs for SCA2.